JAMINAN KEPASTIAN HUKUM TENTANG KEPEMILIKAN TANAH ADAT DAYAK BENUAQ DI KAMPUNG BENTAS KABUPATEN KUTAI BARAT - Samaria Miranda (Journal of Law ( Jurnal Ilmu Hukum ), 2013)
ABSTRACTAccording to Article 22 of the BAL , Property Rights over land can occur as follows : Property Rights on the ground occurs as the determination of the Government ; Land that can be given to the Property by the Government should be the status of the land it controlled directly by the State or that is owned by his change of rights such as the right to use by the applicant and Broking released their rights , so that the status of the land directly controlled by the State . Freehold lands derived from the granting by the Government must be registered in the Agricultural District / Municipality ( National Land Agency ) local , to obtain proof of copyright that is mentioned in the PP. 24 of 1997 ; Property Rights over land occurs because the provisions of law ; Ownership of land can occur because of the determination or statutory provision . In BAL there are provisions that define the rights Belongs to land because of the law , that is, in terms of conversion ; Property Rights over land occur under Customary Law ; According to Article 22 paragraph ( 1 ) of the BAL, the Property Rights Under Customary Law shall be regulated by the government , such as the rights to land under customary law rooted in a forest clearing any part of an indigenous land indigenous peoples.